Stab Wound on Chest - Sitepu, Agustinus (International Journal Labs, 2022)
Trying to figure out how someone died is difficult. Identifying whether a death was caused by suicide, an accident, or a homicide during the first stages of an inquiry is one of the most challenging tasks for a forensic expert and medical staff. The research aims to analyse the stab wound on chest through the lungs. A case was reported. A corpse known by the initials BS which based on the visum request letter dated September 08, 2020, No.K/04/IX/2020/Reskrim on behalf of Binjai Resort Police. On September 08 2020 at 21.00 Western Indonesia Time at the Forensic Room of the Djoelham Hospital, carried out external examination of the corpse and continued internal examination on September 8, 2020 at 22.05 Western Indonesian Time. Head and neck stab wounds are uncommon. The stabbing wound on the left chest is the most hazardous. The tendency is for someone to penetrate the left chest. Furthermore, a murderous person will stab themselves in the left chest. People believed the sufferer would pass away sooner because the majority of the heart is on the left side of the chest.